ACEi to ARNi: "The Switch" An Evidence Based Review - Yusuf Hassan; Zahra Hassan; Ayesha Hassan; Asad A Saleem; Waqas Ahmed (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Heart failure affects approximately 6.5 million adults in the United States, and the cost to healthcare system is tremendous [1]. Effective treatment for this very important disease is constantly evolving. The most significant change in the recent past has been the development of ARNI (Sacubitril/ Valsartan) for treatment of heart failure [2].